NFO speed control of induction motor without using shaft encoder - Petr Kadaník (Communications - Scientific letters of the University of Zilina, 1999)
This article focuses on the design and analysis of a speed-sensorless vector control of induction motor based upon a Natural Field Orientation (NFO). This method allows high-dynamic vector control of PWM VSI fed induction motor. The main merit of NFO is given by no requirement on any speed or position sensor. The presence of a tacho-generator or optical shaft encoder is commonly undesirable. These transducers significantly increase the costs and reduce the reliability and robustness of the overall system. The NFO method doesn’t employ computationally extensive algorithms such as Model Reference Adaptive System or methods based on Kalman filter. Simulation results from a model-based computer-aided design approach using MATLAB/SIMULINK software will be presented.